1983
DOI: 10.2307/1956009
|View full text |Cite
|
Sign up to set email alerts
|

The Illusion of Choice: Defense and Welfare in Advanced Industrial Democracies, 1948-1978

Abstract: Research on the tendency of governments to trade off welfare spending for defense has generated diverse and often contradictory findings. This study attempts to clarify the issue of trade-offs by examining expenditure patterns since 1948 for the four major NA TO allies: United States, United Kingdom, Federal Republic of Germany, and France. When viewed from the perspective of long-term trends in shares of outlays, trade-offs are evident. When short-term changes in expenditure, which are more germane to the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(64 citation statements)
references
References 17 publications
4
56
1
2
Order By: Relevance
“…In addition, Zhang, et al [6] confirmed the positive relationship by measuring the social welfare using inputs and outputs. However, a non-existent relationship has also been found in the literature [13][14][15][19][20][21][22][23]. For instance, Caputo [19] showed defense expenditure has no impact on social welfare in Australia, Sweden, the UK and the US.…”
Section: Empirical Analysismentioning
confidence: 99%
“…In addition, Zhang, et al [6] confirmed the positive relationship by measuring the social welfare using inputs and outputs. However, a non-existent relationship has also been found in the literature [13][14][15][19][20][21][22][23]. For instance, Caputo [19] showed defense expenditure has no impact on social welfare in Australia, Sweden, the UK and the US.…”
Section: Empirical Analysismentioning
confidence: 99%
“…At the federal level, the concept of expenditure tradeoffs was first used by scholars to describe the interrelationship of "guns vs. butter"-that is, the tradeoff between defense and domestic spending (Domke, Eichenberg, and Kelleher, 1983;Mintz, 1989;Mintz and Huang, 1990;Russet, 1982). There has been some consideration of spending tradeoffs at the American state level (Garand and Hendrick, 1991;Nicholson-Crotty, Theobold, and Wood, 2006), though the scholarly literature is less well developed.…”
Section: Developmental Vs Redistributive Spending Areasmentioning
confidence: 99%
“…En varios de ellos se ha com-98 joSé jurADo SánCHEz parado el gasto total en defensa con el gasto total social o público (Szymansky, 1973; Wilensky, 1975;Clayton, 1976;Domke, Eichenberg y Kelleher, 1983). Pero, con el paso del tiempo, lo más frecuente fue que las investigaciones compararan el gasto militar total con uno o varios componentes del gasto social (sanidad y educación, sobre todo, pero también vivienda, asistencia social y departamentos de gasto corriente) (Peroff y Podolak- Warren, 1979;russett, 1982;Mintz y Huang, 1991;Mok y Duval, 1992;Gifford, 2006).…”
Section: Otros Enfoques: Agregado Vs Desagregadounclassified
“…Y, segundo, la de que suponía que el aumento del gasto en defensa afectaría negativamente a la sanidad privada cuando aquél se financiara con aumentos de impuestos en lugar de con incrementos de la oferta monetaria o de la deuda pública, ya que tributos crecientes son más perjudiciales que las otras dos vías de financiarla porque los salarios de los contratos de larga duración no siguen el ritmo de los precios y, por lo tanto, los consumidores tendrán menos ingreso real disponible para destinarlo al cuidado de la salud. Domke, Eichenberg y Kelleher (1983) propusieron varias hipótesis suponiendo que el gasto militar era determinado, esencialmente, por la política exterior y que en el gasto social y total influían las restricciones presupuestarias, los grupos de interés domésticos, la cuantía del ingreso y la situación económica. Mintz (1989) aspiraba a comprobar si los programas militares intensivos en capital detraían recursos de los programas sociales y si los intensivos en trabajo aliviaron las cargas de la sanidad y la educación.…”
Section: La Elaboración De Las Hipótesisunclassified